Safety and immunogenicity of a quadrivalent inactivated subunit non-adjuvanted influenza vaccine: A randomized, double-blind, active-controlled phase 1 clinical trial. Issue 29 (29th June 2021) - Wang, Yanxia; Zhang, Yuhui; Wu, Haofei; Huang, Lili; Yu, Hailong; Xie, Zhiqiang; Zhang, Huiping; Zhang, Wei; Chen, Xiaofen; Zhang, Huan; Zhang, Hongdong; Jia, Chunyu; et al.
Highlights: We assessed the safety/immunogenicity of full-/half-dose subunit NAIIV4 in 6–35 months subjects. We compared the safety/immunogenicity of this subunit vs. a licensed split-virion NAIIV4 in ≥ 3 years subjects. We assessed the effect of the dose of subunit NAIIV4 in 6–35 months toddlers. The full-dose subunit NAIIV4 is safe and can elicit robust immune response in ≥ 6 months subjects. Abstract: Quadrivalent influenza inactivated vaccine (IIV4) is more likely to provide wider protection against yearly circulating influenza viruses than trivalent inactivated influenza vaccine (IIV3). In this study, a total of 320 participants were allocated to four age cohorts (6–35 months, 3–8 years, 9–17 years, and ≥ 18 years; 80 participants/cohort) according to their actual date of birth. Participants in each cohort were randomly assigned to two groups to receive intramuscular injection of the trial vaccine or the comparative vaccine in a one-dose (3–8 years, 9–17 years, and ≥ 18 years) schedule on day 0 or two-dose (6–35 months cohort) schedule on day 0 and 28. The first objective is to evaluate the safety and immunogenicity of the full-dose subunit non-adjuvanted IIV4 (FD-subunit NAIIV4) we developed versus an active-control, China-licensed split-virion NAIIV4, in people ≥ 3 years. The second objective is to evaluate the safety and immunogenicity of FD-subunit NAIIV4 versus the half-dose (HD-subunit NAIIV4) in toddlers aged 6–35 months. Results showed that all adverse reactions noted were rare, mild, and self-limited. In ≥ 3 years cohorts, systemic adverse reactions in FD-subunit NAIIV4 groups were less than the active control split-virion NAIIV4 groups ([Systemic adverse reaction rates (95%CI)], 15.0 (8.6–21.4) versus 19.2(12.1–26.2), p = 0.391). The overall seroprotection efficacy after vaccination were comparable between FD-subunit NAIIV4 and the active control split-virion NAIIV4([Seroprotection rates (95%CI)], H1N1, 99.2(81.3–100.0) versus 94.9(90.9–98.9), p = 0.117; H3N2, 81.7(74.7–88.6) versus 82.1(75.1–89.0), p = 0.939; BV, 75.8(68.2–83.5) versus 74.4(66.4–82.3), p = 0.793; BY, 94.2(90.0–98.4) versus 92.3(87.5–97.1), p = 0.568). Additionally, FD-subunit NAIIV4 has comparable safety and better seroprotection versus that of the half-dose in 6–35 months toddlers groups ([Total adverse reaction rates (95%CI)], 37.5(18.5–56.5) versus 47.5(26.1–68.9), p = 0.366) ([Seroprotection rates (95%CI)], H1N1, 85(56.4–100.0) versus 75.7(47.6–100.0), p = 0.117; H3N2, 50(28.1–71.9) versus 29.7(12.2–47.3), p = 0.070; BV, 75(48.2–100.0) versus 29.7(12.2–47.3), p < 0.001; BY, 75(48.2–100.0) versus 56.8(32.5–81.0), p = 0.091). As a result, the FD-subunit NAIIV4 we developed is safe and effective to provide broader and adequate protection against the circulating influenza viruses during 2018–2019, which could be an essential component of the global preventive strategy for influenza pandemic.